2011
DOI: 10.1116/1.3602470
|View full text |Cite
|
Sign up to set email alerts
|

Atomic structure and optical properties of InAs submonolayer depositions in GaAs

Abstract: Using cross-sectional scanning tunneling microscopy and photoluminescence spectroscopy, the atomic structure and optical properties of submonolayer depositions of InAs in GaAs are studied. The submonolayer depositions are formed by a cycled deposition of 0.5 monolayers InAs with GaAs spacer layers of different thicknesses between 1.5 and 32 monolayers. The microscopy images exhibit InAs-rich agglomerations with widths around 5 nm and heights of up to 8 monolayers. A lateral agglomeration density in the 1012cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 38 publications
2
21
0
3
Order By: Relevance
“…The undoped SML structures are surrounded by a 300-nm-thick GaAs matrix which is then sandwiched by Al x Ga 1−x As barriers to prevent escape of photogenerated carriers. Further details of the growth procedure may be found elsewhere [15,16]. As a reference, an undoped 6.5-nm-thick In 0.18 Ga 0.82 As QW on GaAs was grown at 600…”
Section: Samples and Experimental Detailsmentioning
confidence: 99%
“…The undoped SML structures are surrounded by a 300-nm-thick GaAs matrix which is then sandwiched by Al x Ga 1−x As barriers to prevent escape of photogenerated carriers. Further details of the growth procedure may be found elsewhere [15,16]. As a reference, an undoped 6.5-nm-thick In 0.18 Ga 0.82 As QW on GaAs was grown at 600…”
Section: Samples and Experimental Detailsmentioning
confidence: 99%
“…It has been reported that due to segregation of indium along the growth direction, indium from the bottom layers segregates and coalesces with indium from the top layers and forms In-rich clusters or agglomerates that behave like quantum dots [14]. The desired height and composition are achieved by optimizing the number of deposition cycles as well as by optimizing the GaAs-spacer thickness [6]. The zero-dimensional behavior of SMLQDs has been reported in many works [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The submonolayer (SML) technique is considered as an alternative to the SK growth mode to obtain a higher dot density, smaller aspect ratio, to get a better control of their size and composition, and to avoid the formation of the wetting layer [6,7]. The main idea behind the growth of submonolayer QDs (SMLQDs) is to deposit a fraction of a monolayer (ML) of a low-band-gap material forming monolayer-thick islands which are then covered by a few MLs of a high-band-gap material and the cycle is repeated.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we want to explore the potential of submonolayer (SML) QDs [28] as active media for high-peak-power ultrafast SDLs. The growth of SML superlattices involves a cycled deposition of InAs submonolayers capped with a few monolayers of GaAs, creating a vertically correlated InAs agglomeration with typically high areal densities of the order of 10 12 cm −2 [29]. The heterodimensional morphology of SML QDs combines the beneficial signatures of a zero-dimensional (0D) confinement such as high excitonic gain and very fast gain dynamics with the large DOS and high modal gain usually featured by 2D-confined structures [30].…”
Section: Introductionmentioning
confidence: 99%